CHARACTERIZATION OF MOLLUSCICIDAL COMPONENT OF Moringa oleifera LEAF AND Momordica charantia FRUITS AND THEIR MODES OF ACTION IN SNAIL Lymnaea acuminata - Aparna Upadhyay; Vinay K. Singh; Dinesh K. Singh (Revista do Instituto de Medicina Tropical de São Paulo, 2013)
SUMMARY The molluscicidal activity of the leaf powder of Moringa oleifera and lyophilized fruit powder of Momordica charantia against the snail Lymnaea acuminata was time and concentration dependent. M. oleifera leaf powder (96 h LC50: 197.59 ppm) was more toxic than M. charantia lyophilized fruit powder (96 h LC50: 318.29 ppm). The ethanolic extracts of M. oleifera leaf powder and Momordica charantia lyophilized fruit powder were more toxic than other organic solvent extracts. The 96 h LC50 of the column purified fraction of M. oleifera leaf powder was 22.52 ppm, while that of M. charantia lyophilized fruit powder was 6.21 ppm. Column, thin layer and high performance liquid chromatography analysis show that the active molluscicidal components in M. oleifera leaf powder and lyophilized fruit of M. charantia are benzylamine (96 h LC50: 2.3 ppm) and momordicine (96 h LC50: 1.2 ppm), respectively. Benzylamine and momordicine significantly inhibited, in vivo and in vitro, the acetylcholinesterase (AChE), acid and alkaline phosphatase (ACP/ALP) activities in the nervous tissues of L. acuminata. Inhibition of AChE, ACP and ALP activity in the nervous tissues of L. acuminata by benzylamine and momordicine may be responsible for the molluscicidal activity of M. oleifera and M. charantia fruits, respectively.